2020
DOI: 10.17509/ijal.v10i2.28604
|View full text |Cite
|
Sign up to set email alerts
|

Role of Regional Language Background and Speech Styles on the Production of Voice Onset Time (VOT) in English among Indonesian Multilinguals

Abstract: This paper seeks to contribute to the nature of cross-linguistic transfer in the production of English Voice Onset Time (VOT) by adult multilingual speakers in Indonesia in view of how different regional home languages and speech settings shape the phonetic realizations. Three adult multilinguals participated in this pilot project. They are all learners of English as the third language (L3) at the Department of English of a state university in Malang, Indonesia who acquire different regional home languages – J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Karlina (2020) also argued that the difficulties that happened in Indonesian language are a phonetic language in which there is a direct relationship between spelling and pronunciation. However, students in Indonesia have a variety of language background so that it influences transferring phonological words from their first language to the target language (Zen, 2020). It is in line with the case that happened at the University of Bengkulu in which the students have many regional languages background that affect them in learning and acquiring languages in terms of the phonological process.…”
Section: Introductionsupporting
confidence: 52%
“…Karlina (2020) also argued that the difficulties that happened in Indonesian language are a phonetic language in which there is a direct relationship between spelling and pronunciation. However, students in Indonesia have a variety of language background so that it influences transferring phonological words from their first language to the target language (Zen, 2020). It is in line with the case that happened at the University of Bengkulu in which the students have many regional languages background that affect them in learning and acquiring languages in terms of the phonological process.…”
Section: Introductionsupporting
confidence: 52%
“…From foreign studies, it is found that technologies such as mobile phones, wireless networks, and multimedia are popular in language teaching and learning research. Many researchers had placed RFID tags on top of many objects, and sensors can sense these objects when learners are near, allowing the learners' mobile devices to receive information about these objects [14]. Most of the platforms targeting language learning or context awareness lack and should have empirical studies and rarely do longterm tracking of the systems, but there is no shortage of new technologies introduced and applied.…”
Section: Related Workmentioning
confidence: 99%
“…Language learning in contextual and interactional settings is an essential individual socialization process to master linguistic conventions (Lu et al, 2021). In teaching BIPA to Thai speakers, students in each level of formal education generally do not know Indonesian at all (Jati, 2016), while the core of all multilingual acquisition disciplines is the concept of crosslinguistic transfer (Zen, 2020). In this condition, language transfer can occur, in which speakers use the linguistic elements of their first language when pronouncing a word (Pariyanto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%